Intravenous ibuprofen as an adjunct in acute postoperative pain: A review - Shrestha, Alisha; Huang, Dong (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Postoperative pain can have a significant effect on patient recovery. Studies suggest that 82% patients experience some pain following surgery, of those 47% complaining of moderate pain, 39% experiencing severe to very severe pain. The failure to adequately treat postoperative pain is due to limitations of monotherapy with opioid analgesics. Intravenous ibuprofen is a nonsteroidal antiinflammatory drug with anti-inflammatory, antipyretic, and analgesic properties that may be related to prostaglandin synthetase inhibition and have been shown to reduce opioid requirements with better postoperative pain management. This paper reviews analgesic outcomes of intravenous ibuprofen as an adjunct to opioid for acute postoperative pain in adults. Methods: Relevant studies were searched using cochrane database of systematic reviews, embase and pubmed databases using key words about intravenous ibuprofen and postoperative pain that were appropriate to each database. Results: Tools to assess pain intensity such as visual analog scale, verbal response scale and self-report of pain scores at rest and with movement have been studied. Multimodal approach with preemptive use of nonsteroidal anti-inflammatory drugs for treatment of postoperative pain is considered. Conclusion: Randomized controlled trials and other studies concluded that postoperative pain control protocols can now consider inclusion of intravenous ibuprofen as an adjunct in multimodal approach to offer patients a significant analgesic benefit while reducing the risks associated with opioid administration. Journal of Society of Anesthesiologists of Nepal 2015; 2(1): 21-24